Las relaciones laborales en una trama automotriz argentina - Delfini, Marcelo; Roitter, Sonia (Cuadernos de Relaciones Laborales, 2007)
The aim of the current paper, is to analyze the labour relations developed in the Argentinean productive automotive network through the study of the components of collective bargaining, which were shaped in the Collective Labour Agreements. The emphasis will be mainly on the characteristics that the process and the job organization have. The analysis of the labour relations, in the frame of the relations among the companies, has special relevance as it suggests a connection between the focal point and the suppliers, which affects the outlines of the labour relations developed in the participant enterprises. That allows us to capture them in their real dimension, as it is throughout the course of the productive chain, where the elements that characterize the complexity of the analysis must be looked for.